2020
DOI: 10.1097/sla.0000000000004556
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Pneumatic Compression in Addition to Standard Prophylaxis of Postoperative Venous Thromboembolism in Extremely High-risk Patients (IPC SUPER): A Randomized Controlled Trial

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 30 publications
(54 reference statements)
0
32
0
Order By: Relevance
“…Participants received RBI treatment after surgical operation 24 h. The intermittent pneumatic compression (IPC) device (Zosing, Henan, China) was used to make RBI. The IPC device was described in previous studies [7][8][9] (Fig. 1).…”
Section: Interventionsmentioning
confidence: 99%
“…Participants received RBI treatment after surgical operation 24 h. The intermittent pneumatic compression (IPC) device (Zosing, Henan, China) was used to make RBI. The IPC device was described in previous studies [7][8][9] (Fig. 1).…”
Section: Interventionsmentioning
confidence: 99%
“…8 The more recent publication of the IPC SUPER study classified patients who scored >/¼ 11 points on the Caprini tool 'extremely high risk' patients. 9 This is following some work from the same group (Lobastov et al) from 2016 which demonstrated that there is a strong correlation between Caprini score and the incidence of post-operative DVT. 10 They found DVT risk was increased 18.7-fold for patients with Caprini scores of 9 to 11 and 98.4-fold for scores of 12 to 15 compared with patients with scores of 5 to 8.…”
mentioning
confidence: 72%
“…The trials spanned data collected from 1994 to 2019 with 48 to 2,551 participants ( eTable 1 , http://links.lww.com/CCX/B66 ). Trials were conducted in North America ( 20 , 29 31 , 33 , 34 , 37 ), Europe ( 22 , 35 , 36 , 38 , 39 ), and Asia ( 19 – 21 , 32 , 40 , 41 ). Two trials were conducted in multiple countries ( 20 , 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…We did not confirm the reduced risk of PE observed in these two reviews. The inclusion in our review of recently published RCTs (19)(20)(21)(22)41), of studies using anticoagulants other than heparin and the exclusion of observational studies could explain these discrepancies.…”
Section: Discussionmentioning
confidence: 99%